Resolving structures of transition metal complex reaction intermediates with femtosecond EXAFS. Issue 5 (23rd August 2019) - Britz, Alexander; Abraham, Baxter; Biasin, Elisa; van Driel, Tim Brandt; Gallo, Alessandro; Garcia-Esparza, Angel T.; Glownia, James; Loukianov, Anton; Nelson, Silke; Reinhard, Marco; Sokaras, Dimosthenis; Alonso-Mori, Roberto
Abstract : Femtosecond EXAFS is implemented at an XFEL and can be used to observe short-lived intermediate states of photoexcited transition metal complexes in solution. Abstract : Femtosecond-resolved Extended X-ray Absorption Fine Structure (EXAFS) measurements of solvated transition metal complexes are successfully implemented at the X-ray Free Electron Laser LCLS. Benchmark experiments on [Fe(terpy)2 ] 2+ in solution show a signal-to-noise ratio on the order of 500, comparable to typical 100 ps-resolution synchrotron measurements. In the few femtoseconds after photoexcitation, we observe the EXAFS fingerprints of a short-lived (∼100 fs) intermediate as well as those of a vibrationally hot long-lived (∼ns) excited state.